Experimental and Computational Analysis of 14 Gauge Rooftop Solar PV Mounting Structure against Wind in Pakistan - Arhaam Mubarak; M. Javed Hyder (Engineering Proceedings, 2023)
Fourteen-gauge solar PV mounting structure installations represent 60% of total solar PV installations in Pakistan. At least 34 (1.72%) structures were damaged on 13 June 2021 with an average 56 km/h wind speed on that day. Therefore, a need arose for a thorough analysis of the 14-gauge solar PV mounting structure. Computational analysis was carried out for 14-gauge solar PV mounting structures. The equivalent stress and total deformation in the structure were calculated computationally. Using computational analysis, it was found that 14-gauge solar PV mounting structures deformed at an 80 km/h wind velocity and broke at a 110 km/h wind velocity. Hence, 14-gauge solar PV mounting structures do not fulfil the building code of Pakistan.